The Influence of Technological, Organizational, and Environmental (TOE) Factors on MSME Performance with E-Commerce Adoption as a Mediating Variable and Entrepreneurial Orientation as a Moderating Variable in Surabaya - Desmala Paranti; Nanis Susanti; I.B. Cempena (Lafadz Jaya Publisher, 2024)
Changes in transaction patterns from offline to online require people to be able to adapt and utilize technology to the fullest. The results of the 2020-2023 e-commerce survey show that MSMEs using e-commerce in Indonesia are increasing every year. This growth explains the positive trend of using digital technology in business operations. Therefore, this research needs to be conducted to help other business actors understand the importance of using e-commerce as a strategy to improve marketing performance and increase revenue. This study uses a quantitative method involving 154 MSMEs in Surabaya. researchers distributed questionnaires. The questionnaire consisted of a five-point Likert scale created using Google Form. After completing the data collection, the next stage was to analyze the data using SmartPLS. The results of the data analysis in this study indicate that in the context of technological, organizational and environmental have a significant influence on e-commerce adoption and e-commerce adoption has a significant influence on MSME performance.Meanwhile, entrepreneurial orientation does not have a moderating effect on the relationship between e-commerce adoption and MSME performance.